Mesenchymal stromal cell extracellular vesicles for multiple sclerosis in preclinical rodent models: A meta-analysis - Xun, Chengfeng; Deng, Huiyin; Zhao, Jing; Ge, Lite; Hu, Zhiping (Frontiers in Immunology, 2022)
Introduction: Extracellular vesicles (EVs), especially mesenchymal stem (stromal) cell-derived EVs (MSC-EVs), have gained attention as potential novel treatments for multiple sclerosis (MS). However, their effects remain incompletely understood. Thus, the purpose of this meta-analysis was to systematically review the efficacy of MSC-EVs in preclinical rodent models of MS. Methods:We searched PubMed, EMBASE, and the Web of Science databases up to August 2021 for studies that reported the treatment effects of MSC-EVs in rodent MS models. The clinical score was extracted as an outcome. Articles were peer-reviewed by two authors based on the inclusion and exclusion criteria. This meta-analysis was conducted using Stata 15.1 and R. Results: A total of twelve animal studies met the inclusion criteria. In our study, the MSC-EVs had a positive overall effect on the clinical score with a standardized mean difference (SMD) of -2.17 (95% confidence interval (CI)):-3.99 to -0.34, P = 0.01). A significant amount of heterogeneity was observed among the studies. Conclusions: This meta-analysis suggests that transplantation of MSC-EVs in MS rodent models improved functional recovery. Additionally, we identified several critical knowledge gaps, such as insufficient standardized dosage units and uncertainty regarding the optimal dose of MSC-EVs transplantation in MS. These gaps must be addressed before clinical trials can begin with MSC-EVs.